2022
DOI: 10.3390/healthcare10101836
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Medical Reliability of Videos on Social Media: Detailed Analysis of the Quality and Usability of Four Social Media Platforms (Facebook, Instagram, Twitter, and YouTube)

Abstract: Introduction: In recent years, the internet and social media have become the primary source for patients to research their medical conditions. Given the billions of links that result from research, it has become increasingly important how medically high quality the priorities of the search algorithms are. This study aims to examine the medical quality of videos on social media. Material and Method: A new Gmail account was never used, and Facebook, Instagram, Twitter, and YouTube accounts were opened. The word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Additionally, under the univariate and multivariate linear regression models, videos posted by patient accounts and patient experience videos were significant for a negative correlation with DISCERN score. These findings are supported by similar studies that have found that patient‐derived media is associated with lower content quality via the DISCERN instrument 33,34 . Patient‐derived videos may provide patients with reassurance and valuable perspectives but may introduce misunderstandings based on anecdotal experiences 35,36 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, under the univariate and multivariate linear regression models, videos posted by patient accounts and patient experience videos were significant for a negative correlation with DISCERN score. These findings are supported by similar studies that have found that patient‐derived media is associated with lower content quality via the DISCERN instrument 33,34 . Patient‐derived videos may provide patients with reassurance and valuable perspectives but may introduce misunderstandings based on anecdotal experiences 35,36 .…”
Section: Discussionsupporting
confidence: 62%
“…These findings are supported by similar studies that have found that patient‐derived media is associated with lower content quality via the DISCERN instrument. 33 , 34 Patient‐derived videos may provide patients with reassurance and valuable perspectives but may introduce misunderstandings based on anecdotal experiences. 35 , 36 While clinician expertise is not expected from layperson accounts, these anecdotes can significantly impact the future decision‐making of other patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there has been an enormous increase in the demand for medical seeking information by the general population and young students (Chen & Wang, 2021; Grajales 3rd et al., 2014; Hassona et al., 2016). YouTube, a global social media platform, is well‐accepted for sharing online videos, thus facilitating healthcare professionals to provide general information to their respective stakeholders (Altan Şallı & Egil, 2020; Gurler & Buyukceran, 2022; Sterling et al., 2017; Yildirim & Kocaelli, 2023). It further enables individuals to share information in both audio and visual forms, making it more popular and straightforward for communication.…”
Section: Introductionmentioning
confidence: 99%
“…While recent studies on healthcare-related YouTube videos have revealed that they generally lack the ability to accurately depict medical diagnoses and treatments for common illnesses and procedures, limited research has explored the ease with which patients can comprehend and absorb this information when watching these videos [ 5 ]. The increasing trend of using YouTube for healthcare information, coupled with the rise in unreliable and misleading videos, can lead to confusion and frustration among both healthcare providers and patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%